Intramuscular Contributions to Low-Frequency Force Potentiation Induced by a High-Frequency Conditioning Stimulation - Cheng, Arthur J.; Neyroud, Daria; Kayser, Bengt; Westerblad, Håkan; Place, Nicolas (Frontiers in Physiology, 2017)
Electrically-evoked low-frequency (submaximal) force is increased immediately following high-frequency stimulation in human skeletal muscle. Although central mechanisms have been suggested to be the major cause of this low-frequency force potentiation, intramuscular factors might contribute. Thus, we hypothesized that two intramuscular Ca2+-dependent mechanisms can contribute to the low-frequency force potentiation: increased sarcoplasmic reticulum Ca2+ release and increased myofibrillar Ca2+ sensitivity. Experiments in humans were performed on the plantar flexor muscles at a shortened, intermediate, and long muscle length, and electrically evoked contractile force and membrane excitability (i.e., M-wave amplitude) were recorded during a stimulation protocol. Low-frequency force potentiation was assessed by stimulating with a low-frequency tetanus (25 Hz, 2 s duration), followed by a high-frequency tetanus (100 Hz, 2 s duration), and finally followed by another low-frequency tetanus (25 Hz, 2 s duration) tetanus. Similar stimulation protocols were performed on intact mouse single fibres from flexor digitorum brevis muscle, whereby force and myoplasmic free [Ca2+] ([Ca2+]i) were assessed. Our data show a low-frequency force potentiation that was not muscle length-dependent in human muscle and it was not accompanied by any increase in M-wave amplitude. A length-independent low-frequency force potentiation could be replicated in mouse single fibres, supporting an intramuscular mechanism. We show that at physiological temperature (31°C) this low-frequency force potentiation in mouse fibres corresponded with an increase in sarcoplasmic reticulum (SR) Ca2+. When mimicking the slower contractile properties of human muscle by cooling mouse single fibres to 18°C, the low-frequency force potentiation was accompanied by minimally increased SR Ca2+ release and hence it could be explained by increased myofibrillar Ca2+ sensitivity. Finally, introducing a brief 200 ms pause between the high- and low-frequency tetanus in human and mouse muscle revealed that the low-frequency force potentiation is abolished, arguing that increased myofibrillar Ca2+ sensitivity is the main intramuscular mechanism underlying the low-frequency force potentiation in humans.